2017
DOI: 10.1681/asn.2016040474
|View full text |Cite
|
Sign up to set email alerts
|

Pals1 Haploinsufficiency Results in Proteinuria and Cyst Formation

Abstract: The nephron is the basic physiologic subunit of the mammalian kidney and is made up of several apicobasally polarized epithelial cell types. The process of apicobasal polarization in animal cells is controlled by the evolutionarily conserved Crumbs (CRB), Partitioning-defective, and Scribble protein complexes. Here, we investigated the role of protein associated with LIN-7 1 (Pals1, also known as Mpp5), a core component of the apical membrane-determining CRB complex in the nephron. Pals1 interacting proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 52 publications
6
67
0
Order By: Relevance
“…while a cell may have mRNA from only one allele at a particular time, it may gain mRNA from the other allele a short time later if another transcriptional event occurs. For Mpp5 , this conclusion is in line with the fact that the reported haploinsufficient phenotype is thought to be caused by overall reduced dosage(Straight et al 2004;Weide et al 2017) rather than by a special subpopulation of cells with monoallelic expression. More generally, this scenario links the observation of transcriptional bursting with that of random monoallelic expression, as put forward by Sandberg et al(Reinius and Sandberg 2015;Reinius et al 2016) , and explains why we (and others previously(Gendrel et al 2014; ) observed the co-occurrence of cells with one and two transcription sites in the same population.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…while a cell may have mRNA from only one allele at a particular time, it may gain mRNA from the other allele a short time later if another transcriptional event occurs. For Mpp5 , this conclusion is in line with the fact that the reported haploinsufficient phenotype is thought to be caused by overall reduced dosage(Straight et al 2004;Weide et al 2017) rather than by a special subpopulation of cells with monoallelic expression. More generally, this scenario links the observation of transcriptional bursting with that of random monoallelic expression, as put forward by Sandberg et al(Reinius and Sandberg 2015;Reinius et al 2016) , and explains why we (and others previously(Gendrel et al 2014; ) observed the co-occurrence of cells with one and two transcription sites in the same population.…”
supporting
confidence: 69%
“…These genes were selected to represent genes with ( Aebp1 , Churc1 , Lyplal1 ) and without ( Aqp11 , Mpp5 , Podxl, Prcp, Stard5 ) putative random monoallelic expression (Gendrel et al 2014;Li et al 2012;Zwemer et al 2012) and with different expression levels, patterns and chromosomal locations. Some of the chosen genes were also linked to specific kidney disease phenotypes ( Aqp11 (Ishibashi, Hara, and Kondo 2009) , Mpp5 (Straight et al 2004;Weide et al 2017) , Prcp (Maier et al 2017) ) ( Table S4). As expected, these genes were typically expressed at much lower levels than Xist and punctate individual mRNA spots could not be as readily observed in low magnification scans.…”
Section: Snv-specific Detection Of Rnas In Mouse Tissue Using Single mentioning
confidence: 99%
“…These genes were selected to represent genes with ( Aebp1 , Churc1 , Lyplal1 ) and without ( Aqp11 , Mpp5 , Podxl , Prcp , Stard5 ) putative random monoallelic expression [3841] and with different expression levels, patterns and chromosomal locations. Some of the chosen genes were also linked to specific kidney disease phenotypes ( Aqp11 [54], Mpp5 [55,56], Prcp [57] ) (Methods, S4 Table). As expected, these genes were typically expressed at much lower levels than Xist and punctate individual mRNA spots could not be as readily observed in low magnification scans.…”
Section: Resultsmentioning
confidence: 99%
“…1h). The molecular components of the slit diaphragm are highly conserved between the nephrocytes in D. melanogaster and podocytes in vertebrates (Weavers et al 2009;Zhuang et al 2009) and Drosophila nephrocytes have recently been used as a model system to study podocyte function and disease (Fu et al 2017;Helmstädter and Simons 2017;Na et al 2015;Tutor et al 2014;Weide et al 2017). Podocytes are localized at the glomerulus (G), a primary urine-producing apparatus.…”
Section: Introductionmentioning
confidence: 99%